Numerical Simulation Study on the Response of Ship Engine Room Structure Under Fire Based on Thermo-Mechanical Coupling Model - Yuechao Zhao; Zeya Miao; Shouye Wang; Dihao Ai (Fire)
Ship structures may collapse or be severely deformed during a fire. To precisely assess the post-fire structural integrity of ships, in this study, a thermal–mechanical coupling data interface was created, employing a significant eddy simulation algorithm for fire dynamics and a technique to analyze the structural thermal–mechanical coupling reaction. PyroSim was utilized to build a fire scenario, exporting 3D data through the device’s own program, and then the ANSYS thermal–mechanical coupling model was employed to study the spatial temperature distribution under fire-induced conditions. Data from the three-dimensional spatial temperature field served as the boundary condition for the determination of the structural temperature burden. Building on this, an analysis was conducted on the structural response of the intricate two-story interior compartment under fire conditions. The results showed that the location of the fire source and the structural distribution of the mechanical equipment inside the cabin had a great influence on the temperature and combustion heat, followed by the ventilation conditions, while the temperature variations in the parallel dual fuel tanks were greatly influenced by the stack effect. By comparing the stress and strain of the two-layer cabin under normal and fire conditions, the damage and mechanisms associated with important positions in the cabin under fire conditions were revealed.